Reinventing the Learner: The Influence of Existentialist Philosophy on Modern Education - Astria, Yeni; Angraini, Dewi; Sunayah, Sunayah; Jelestari, Nerma; Septi, Elni (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This article examines the influence of existentialist philosophy on the concept of modern education, specifically in terms of freedom, responsibility, and self-awareness among learners. Using a Systematic Literature Review (SLR) method, the author analyzes 15 relevant scholarly articles to examine how existentialist principles are applied in educational settings. The findings reveal that existentialism promotes a more humanistic and student-centered educational approach, allowing learners to determine their own learning paths with autonomy and accountability. Teachers act as facilitators who guide students in developing reflective, critical, and authentic character traits. Although the existentialist approach has great potential to improve educational quality, its implementation requires a flexible system and adaptive teachers. This article affirms that existentialist philosophy remains relevant in shaping a more meaningful and contemporary education system.